Novel spa and Multi-Locus Sequence Types (MLST) of Staphylococcus Aureus Samples Isolated from Clinical Specimens in Korean - Yae Sung Mun; You Jin Hwang (MDPI AG, 2019)
Staphylococcus aureus bacteremia is one of the most frequent and severe bacterial infections worldwide. The increased incidence of S. aureus infections with a diverse pattern of S. aureus protein A (spa) types across different geographic regions is a global challenge. This study investigated a novel spa type of methicillin-resistant S. aureus in a clinically isolated specimen. A total of 109 clinical S. aureus samples were subjected to 19 sets of antimicrobial susceptibility testing using the Kirby−Bauer disk diffusion method. Molecular typing was performed with S. aureus protein A (spa) and multi-locus sequence types (MLST) via polymerase chain reaction and sequencing. The methicillin-resistant S. aureus samples in our study accounted for 55.05% (60/109) of the total. A novel spa type was detected in five (5/60) strains. This gh22 isolate was identified in antimicrobial susceptibility tests of 15 kinds of antibiotics. Antibiotic resistance genes included mecA, TEM, aac(6′)-aph(2”), ermA, and tetM. Eleven S. aureus samples were classified as t2460, t338, t324, t693, five unknown spa types (new spa types), and undefined MLST (novel MLST). We report a high prevalence rate of t2460 methicillin-resistant S. aureus samples in our country. Additionally, novel spa gh22, MLST ST4613, and clonal compact CC5-type strains (T1:M1:B1:B1:M1:E1:K1, r26:r17:r34:r34:r17:r13:r16, mlst;1:4:1:4:559:495:10) showing multidrug resistance were identified among S. aureus samples.